Education of Teachers and Experience of the “Active School” - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2002)
The comparative analysis of the works of foreign education scientists shows that there are many similarities in teacher education problems abroad and in Lithuania: lack of integration between pedagogical theory and practice; too little effort to teach the future teachers to teach effectively and use modern active teaching methods; the role of practice work in teacher education is often underestimated and other problems. Based on comparative analysis the article reviews the main principles of education, the content of teaching forms and methods of its organization, attitudes toward the child, requirements for the education of teachers, problems of the pedagogical intercommunication and their solution in the “active school”. So studying of the theory and practice of “active school” can help to solve these problems of modem teacher education.
Keywords: History of education; “active school”; teacher education; pedagogical theories; active teaching methods.